Intercultural Communication Behavior In Religious Rituals - I Gusti Ayu Ratna Pramesti Dasih Ratna Pramesti; I Gusti Ayu Diah Prameswara Padawati Indraswari; I Dewa Gede Putu Budiyasa (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
Intercultural communication is a process of exchanging symbolic systems that are able to guide human behavior to perceive messages. Intercultural communication can be reflected in ritual communication activities. Ritual communication is carried out by communities who carry out cultural ceremonies and traditions throughout the year and their lives, to express words or display certain symbolic behaviors. Messages in ritual communication are usually hidden and confusing, sometimes having multiple meanings, depending on tradition and culture. The belief system, religion, and worship greatly influence the perception of messages in ritual communication. The process of ritual communication occurs because of supporting factors such as liturgical rites, belief systems, and worship systems. A two-way communication process is applied to support religious, social and ethical-based ritual communication activities. Social interaction is built to establish communication so that it has implications for strengthening religious attitudes, social communicative actions, and cultural values.